1995
DOI: 10.5032/jae.1995.04010
|View full text |Cite
|
Sign up to set email alerts
|

Learning And Teaching Styles Of Student Teachers In The Northwest

Abstract: Learning style refers to the predominant and preferred manner in which individuals take-in, retain, process, and recall information. Teaching style is defined as the predilection toward behavior in the teaching-learning exchange that comes from attitudes, aspirations, and, personal and social histories and cultures. The purpose of this descriptive study was to describe the preferred learning style and teaching style of student teachers in agricultural education at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
3
17
1
Order By: Relevance
“…Theory suggests that small groups are more satisfying for extraverted learners who thrive in group environments and learn best by sharing their thoughts with others (Jung, 1971). The findings of this study add to the divergent field of literature pertaining to learning style in both agricultural education as well as other educational disciplines (Cano, et al, 1992;Garton et al, 1999;Marrison & Frick, 1994;Thornton, Haskell, & Libby, 2006;Whittington & Raven, 1995) and confirms the findings of Marrison and Frick (1994) who found that learning style produced no significant differences in academic achievement.…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 78%
See 2 more Smart Citations
“…Theory suggests that small groups are more satisfying for extraverted learners who thrive in group environments and learn best by sharing their thoughts with others (Jung, 1971). The findings of this study add to the divergent field of literature pertaining to learning style in both agricultural education as well as other educational disciplines (Cano, et al, 1992;Garton et al, 1999;Marrison & Frick, 1994;Thornton, Haskell, & Libby, 2006;Whittington & Raven, 1995) and confirms the findings of Marrison and Frick (1994) who found that learning style produced no significant differences in academic achievement.…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 78%
“…They are fascinated with scientific ideas and are future oriented. (Shindler & Yang, 2003) Many agricultural education scholars have focused their work on the impact of learning styles on various attributes including teaching impact, learning outcomes, satisfaction with schooling and mentoring experiences, and creative thinking (Cano & Garton, 1994;Cano et al, 1992;Dyer & Osborne, 1996;Friedel & Rudd, 2006;Garton et al, 1999;Lambert et al, 2010;Marrison & Frick, 1994;Whittington & Raven, 1995). The wider body of educational research (Hansen & Stansfield, 1982;McDonald, 1984;Mehdikhani, 1983;Miller, 1991;Paradise & Block, 1984) has also used learning styles as a key variable for examining the impact of style upon similar constructs, with similar results -no significant differences between groups.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…This finding is consistent with Raven et al (1993) and Whittington and Raven (1995), who found a majority of preservice teachers preferred to teach using studentcentered methods. Thus, it may be reasonable to conclude that preservice teachers were able to follow through with their preferred method and extend student-centered lessons into the authentic experience -their student teaching internship.…”
Section: Conclusion and Recommendationssupporting
confidence: 81%
“…Similarly, Raven, Cano, Garton, and Van Shelhamer (1993) found 100% of the preservice teachers at Montana State University preferred using a learner-centered teaching style, while about 75% of preservice teachers at The Ohio State University preferred to use a learner-centered teaching style. Additionally, Whittington and Raven (1995) examined the preferred teaching styles of student teachers at Montana State University and the University of Idaho. Results showed overwhelmingly, the majority (93.5%) of student teachers at both universities preferred to use a learner-centered teaching style.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%